Powstanie i ewolucja polskiego prawa dotyczącego pomocy publicznej dla przedsiębiorców - Siudak, Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
State aid for entrepreneurs is an integral element of economic policy of every country. Its range and possible forms are the subject of hard discussions carried out for many years, also in the EU countries, what allowed achieving the common attitude. The Polish membership of the European Union was dependent on the harmonisation of the law, also in the field of State aid that is a part of the EU law of competition. The transposition of the EU rules to Polish law wasn't an easy process. Passing in Poland the first bill concerning conditions of admittance and supervision of State aid for entrepreneurs was a success. Beside its main aims, such as reducing disadvantageous tendency in the range of State aid administration, increasing the rationality of public expenses, creating the system of monitoring and supervision of State aid for entrepreneurs and harmonisation of the Polish law with the EU law and international standards, it had also an educational purpose. It allowed initiating the process of shaping the awareness of State aid and its accessibility within entrepreneurs. Further modifications of the law were the consequence of the demand for cohesion conditions fulfilment in the range of State aid for entrepreneurs. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 118-132